Congélation de viande de porc sous champ électrique : effet sur la taille et la structure des cristaux de glace - Xanthakis, Epameinondas; Chevallier, Sylvie; LeBail, Alain (My University, 2013)
A static electric field is expected to modify the orientation of polar molecules such as water. This paper presents original results obtained in the case of freezing of pork meat (filet mignon) under static electric field using a lab scale miniature freezer. A control sample has been compared to meat frozen with 12 kV electric field (approx. 6·103 kV/m). The degree of supercooling during freezing was reduced with increasing static electric field; values of 3.93 ± 1.3°C and 1.92 ± 1.45°C were observed for the control and the sample frozen at 12 kV respectively. The average size of the ice crystals was significantly reduced with increasing electric field; values of 32.79 ± 4.04 µm and 14.55 ± 8.20 µm were observed for the control and the sample frozen at 12 kV respectively. These original results demonstrate clearly the advantage of freezing under static electric field which appears as a promising and innovative freezing process.
Keywords: Meat; Pork; Crystal; Freezing; Electric field